PENGARUH CHALLENGES STRESSOR TERHADAP TASK PERFORMANCE DENGAN SELF EFFICACY DAN MOTIVATION TO WORK SEBAGAI VARIABLE MEDIASI - Bianka Andriyani (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
SUMMARY Human resources is seen by the company as a valuable asset that must be maintained existence. In the process, the employee will face a variety of conditions that will impact the results of the work done by employees. One of the conditions experienced by the employee is stress. In this study, researchers took the challenge variable stressor as a challenge stressor forms of stress because stress is a condition that a positive impact on employee performance. With good employee performance, expected performance of the company as a whole will be better. This study examined the effect of stressors challenge to the task performance with self-efficacy and motivation to work as a mediating variable. In this case, the researchers suspect stressor challenge will be a positive influence on task performance of employees. In this study, researchers recruited variable self-efficacy and motivation to work as a mediating variable that will mediate the effect of stressors on task performance challenges. The sampling method using a non-probability sampling, that every element in the population do not have the opportunity or the same chance to be selected as a sample. Non-probality sampling method used in this study is a convenience method to select members of the population that is most easily found as respondents. Sampling was done by purposive sampling, ie sampling with certain criteria in order to samples taken in accordance with the purpose of research. The population of this research is employees at one company in DIY as respondent for allegedly will be able to provide a response to stressors experienced Challenge to Task Performance. Keywords: Challenge Stressors, Self Efficacy, Motivation to Work, and Task Performance